2022
DOI: 10.1139/er-2020-0106
|View full text |Cite
|
Sign up to set email alerts
|

Review of studies analysing glyphosate and aminomethylphosphonic acid (AMPA) occurrence in groundwater

Abstract: The herbicide glyphosate (N-phosphonomethylglycine) has been the most commonly applied herbicide worldwide for the past 40 years. This review aims to present and discuss the state of knowledge concerning groundwater contamination by glyphosate and its metabolite, aminomethylphosphonic acid (AMPA). A dataset of 48 reports and articles reporting glyphosate and AMPA detection in groundwater worldwide was constructed from published literature. Specific attention was given to the analysis of available studies on gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 101 publications
(140 reference statements)
0
7
0
Order By: Relevance
“…In 2017, the European Union (EU) controversially voted to re-license glyphosate use for a limited period of five years and a recent extension, until December 2023, was granted to allow the European Food Safety Authority (EFSA) to conclude its examination on this timely and debated issue. Analogously, raising concerns about the chronic toxicity associated with AMPA has led to its inclusion with PMG in pollution monitoring programs [16].…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, the European Union (EU) controversially voted to re-license glyphosate use for a limited period of five years and a recent extension, until December 2023, was granted to allow the European Food Safety Authority (EFSA) to conclude its examination on this timely and debated issue. Analogously, raising concerns about the chronic toxicity associated with AMPA has led to its inclusion with PMG in pollution monitoring programs [16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, microbial degradation of glyphosate in soil results in the accumulation of AMPA in soil, plants, and animal products. 18 AMPA is highly soluble in water, more persistent in the environment than glyphosate, 83 and therefore frequently detected at higher concentrations than glyphosate in most hydrological settings, with groundwater and soil water samples having the highest values. 81 Tracer studies in Canada have shown that AMPA in groundwater is mainly derived from glyphosate degradation rather than wastewater sources, such as those contaminated with phosphonates.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, AF does not include the particular soil structure heterogeneity that might lead to sitespecific solute bypass. Moreover, it does not account for single heavy rainfall events, which could have had an effect on moving the herbicide through the soil matrix down to 70 cm depth (Carretta et al, 2021b). Finally, the finding of GLP and AMPA below 30 cm can be due to herbicide interception by the aboveground vegetation, its following translocation into belowground tissues, and its likely release by dead roots below the topsoil (Laitinen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%